Pengaruh Implementasi Akuntansi Lingkungan terhadap Kinerja Perusahaan: Systematic Literature Review - Tamala Salavia; Putri Seftiana Fitri; Dien Noviany Rahmatika (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
Environmental accounting, also known as “Green Accounting” or “Evironmental Accounting”, refers to the process by which businesses or companies incorporate environmental costs into their accounting procedures. Environmental costs are the result of actions that have an impact on the quality of the environment, whether financially or not. The aim of this research is to look at the function, application and impact of environmental accounting on environmental and business sustainability. This research method was carried out using a Systematic Literature Review (SLR). This approach is used to examine and review all research. A total of 52 articles were analyzed in this research. Research Results Environmental accounting has a positive impact on a number of factors related to the sustainability of a business entity, especially company performance through the use of social responsibility as a mediator. Research on environmental accounting Even though Indonesia is a strong country, it still needs improvement because there is not much research there and the topics discussed are limited. The results of this research have consequences for environmental management initiatives and actions that are based on green innovation or environmentally friendly principles and can develop further.